Bacterial 16S Sequence Analysis of Severe Caries in Young Permanent Teeth - Gross, Erin L; Leys, Eugene J; Gasparovich, Stephen R; Firestone, Noah D; Schwartzbaum, Judith A; Janies, Daniel A; Asnani, Kashmira; Griffen, Ann L (Journal of Clinical Microbiology, 2010)
Previous studies have confirmed the association of the acid producers Streptococcus mutans and Lactobacillus spp. with childhood caries, but they also suggested these microorganisms are not sufficient to explain all cases of caries. In addition, health-associated bacterial community profiles are not well understood, including the importance of base production and acid catabolism in pH homeostasis. The bacterial community composition in health and in severe caries of the young permanent dentition was compared using Sanger sequencing of the ribosomal 16S rRNA genes. Lactobacillus species were dominant in severe caries, and levels rose significantly as caries progressed from initial to deep lesions. S. mutans was often observed at high levels in the early stages of caries but also in some healthy subjects and was not statistically significantly associated with caries progression in the overall model. Lactobacillus or S. mutans was found either at low levels or not present in several samples. Other potential acid producers observed at high levels in these subjects included strains of Selenomonas, Neisseria, and Streptococcus mitis. Propionibacterium FMA5 was significantly associated with caries progression but was not found at high levels. An overall loss of community diversity occurred as caries progressed, and species that significantly decreased included the Streptococcus mitis-S. pneumoniae-S. infantis group, Corynebacterium matruchotii, Streptococcus gordonii, Streptococcus cristatus, Capnocytophaga gingivalis, Eubacterium IR009, Campylobacter rectus, and Lachnospiraceae sp. C1. The relationship of acid-base metabolism to 16S rRNA gene-based species assignments appears to be complex, and metagenomic approaches that would allow functional profiling of entire genomes will be helpful in elucidating the microbial pathogenesis of caries.